Phakopsora euvitis Causes Unusual Damage to Leaves and Modifies Carbohydrate Metabolism in Grapevine - Nogueira Júnior, Antonio F.; Ribeiro, Rafael V.; Appezzato-da-Glória, Beatriz; Soares, Marli K. M.; Rasera, Júlia B.; Amorim, Lilian (Frontiers in Plant Science, 2017)
Asian grapevine rust (Phakopsora euvitis) is a serious disease, which causes severe leaf necrosis and early plant defoliation. These symptoms are unusual for a strict biotrophic pathogen. This work was performed to quantify the effects of P. euvitis on photosynthesis, carbohydrates and biomass accumulation of grapevine. The reduction in photosynthetic efficiency of the green leaf tissue surrounding the lesions was quantified using the virtual lesion concept (β parameter). Gas exchange and responses of CO2 assimilation to increasing intercellular CO2 concentration were analysed. Histopathological analyses and quantification of starch were also performed on diseased leaves. Biomass and carbohydrate accumulation were quantified in different organs of diseased and healthy plants. Rust reduced the photosynthetic rate, and β was estimated at 5.78, indicating a large virtual lesion. Mesophyll conductance, maximum rubisco carboxylation rate, and regeneration of ribulose-1,5-bisphosphate dependent on electron transport rate were reduced, causing diffusive and biochemical limitations to photosynthesis. Hypertrophy, chloroplast degeneration of mesophyll cells and starch accumulation in cells close to lesions were observed. Root carbohydrate concentration was reduced, even at low rust severity. Asian grapevine rust dramatically reduced photosynthesis and altered the dynamics of production and accumulation of carbohydrates, unlike strict biotrophic pathogens. The reduction in carbohydrate reserves in roots would support polyetic damage on grapevine, caused by a polycyclic disease.